Return to Sports Following Lateral Ankle Sprain in Professional Athletes: A Review of Articles: Study of return to sports after Lateral Ankle Sprains - Daneshmandi, Hassan; Asadi , Sara; Fadaei Dehcheshmeh, Milad (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Lateral ankle sprain (LAS) is one of the most common injuries during physical activity. The present study investigated the return to sport after lateral ankle sprains in professional athletes due to the high prevalence of this injury and the need to pay attention to athletes’ return to the same level of sports performance as before the injury. Materials and Methods: In this study, a comprehensive review of the published papers have been done considering English specialized keywords, including physical therapy, sport-specific movement, return to sport, ankle injuries, ligament injuries, return to play, lower extremity, ankle sprain, recurrent injury, ankle, sports injury, lateral ankle instability, chronic ankle instability, athlete, lateral ankle sprain. Therefore, databases, i.e., Science Direct, Scopus, Pedro, Google Scholar, PubMed, SID, ISC, Madlib, Magiran, and Irandoc, were explored, and those researches were published between 2000 to April 2022 about the return to sport and LAS injuries were studied. Results: After searching in the mentioned databases, the abstract of 370 articles on return to sport after LAS was first found, and then the full text of 148 related papers was studied. After reviewing them based on the inclusion and exclusion criteria and eliminating duplicate items, 47 articles were scrutinized. Finally, 11 papers about the return to sport after LAS injury were identified. Most studies reported that the recommended methods reduce the time to return to sport. In this regard, some studies set a time to return to sport, and some did not report the exact time. Studies emphasized using specific tests and criteria for evaluating athletes to enter the final stage of rehabilitation as the most important principle of safely returning to sport. Conclusion: Athletes’ return to physical activity should be followed to allow them to safely return to sport while minimizing the risk of recurrent injuries. Determining specialized criteria and tests for high and diverse populations in sports, especially those involved with lateral ankle sprains, is the key to success in a safer return to sport. However, most studies have been conducted in limited populations and disciplines, and researchers must perform more research in this area.